2003
DOI: 10.1177/1461444803005002001
|View full text |Cite
|
Sign up to set email alerts
|

Children's Use of the Internet: Reflections on the Emerging Research Agenda

Abstract: As domestic access to the internet reaches the mass market in industrialised countries, this article identifies and evaluates the emerging research agenda, focusing particularly on children and young people. The nature of children's use of the internet generates public anxieties which both guides and undermines research, complicating the already challenging study of children within the privacy of the home. The body of empirical work reviewed is still small, but already key questions of academic and policy sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
0
18

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 286 publications
(192 citation statements)
references
References 42 publications
(52 reference statements)
4
170
0
18
Order By: Relevance
“…Subrahmanyam et al (2001) raises the further issue, not of how family dynamics mediate computer use but instead of how computer use mediates family relationships. As Kraut et al (1998) found, in the early days of internet adoption, greater use of the internet was associated with subsequent declines in family communication although subsequent findings have challenged this conclusion (Livingstone, 2003).…”
Section: Consequences Of Domestic Regulation Of Media Usementioning
confidence: 90%
“…Subrahmanyam et al (2001) raises the further issue, not of how family dynamics mediate computer use but instead of how computer use mediates family relationships. As Kraut et al (1998) found, in the early days of internet adoption, greater use of the internet was associated with subsequent declines in family communication although subsequent findings have challenged this conclusion (Livingstone, 2003).…”
Section: Consequences Of Domestic Regulation Of Media Usementioning
confidence: 90%
“…on different levels of access to modern computers and Internet technology. Generally, studies dealing with the second-level digital divide, that is how and for what purposes people use computers and the Internet, point out how difficult it is to study this 'technological black box' (see Attewell, 2001;Natriello, 2001;Livingstone, 2003). Unfortunately, the GSOEP does not contain measures on user profiles either.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, na realidade, o uso dessas tecnologias pelas pessoas prevalece muito menos do que esses entusiastas imaginam. De fato, embora os aplicativos da internet possam muito bem estar profundamente embutidos no tecido social da classe média e nas vidas tecnologicamente privilegiadas dos acadêmicos e de seus filhos, para muitos jovens, a internet continua claramente constituindo uma "mídia frá-gil", usada (quando é usada) de modos muito mais limitados, esporá-dicos e geralmente conservadores (Livingstone, 2003). Assim, apesar do prestígio de que esses aplicativos gozam nas mentes e imaginações de alguns acadêmicos e formuladores de políticas, são poucas as pessoas que criam e mantêm seus próprios sites, escrevem e atualizam seus próprios blogs e participam ativamente de comunidades virtuais (OXIS, 2007).…”
Section: Educunclassified